IMPROVING STUDENTS’ LEARNING OUTCOMES IN THE THEME OF “PERISTIWA DALAM KEHIDUPAN” THROUGH VIDEO – ASSISTED STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) MODEL AT GRADE V ELEMENTARY SCHOOL - Fahriza Deaz Ismaya; Murtono; Deka Setiawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the application of student team achievement division (STAD) model assisted by instructional video media to improve students’ learning outcomes. This study utilized classroom action research (CAR) consisting of two cycles. Each cycle consisted of four stages, namely planning, implementing actions, observing, and reflecting. The subjects of this study were 21 fifth grade students at SD 5 Gondoharum, Kecamatan Jekulo, Kabupaten Kudus. There were 13 male students and 8 female students in this study. Data were collected through observations, interviews, tests, and documentation. The results of observations revealed that the teacher’s skills in managing learning increased from a percentage of 76% (Good) in cycle I to 87% (Very Good) in cycle II. Meanwhile, students’ learning outcomes in the pre-cycle aspects of IPS content reached the completeness of 47.6% (need guidance). It increased in cycle I to 71.4% (good) and in cycle II to 85.7% (good). Moreover, the learning outcomes in pre-cycle knowledge aspects of Bahasa Indonesia content reached the completeness of 42.9% (need guidance). Then, it increased in cycle I to 66.7% (need guidance) and in cycle II to 90.5% (very good). Finally, the students’ learning outcomes in the skills aspects in cycle I reached an average of 76.2% (enough) and increased in cycle II to 85.7% (good).